Pengembangan Usaha Berbasis Home Industry melalui Transformasi Pertanian di Desa Gampong Teungoh - Ulfia, Niza; Umaina, Savana Meilia; Umairah, Shila; Humaira, Humaira; Munira, Fitria Rizqi; Munawarah, Munawarah; Marpaung, Tiara Aulia Ramdhani; Anggraini, Dini; Oluzuon, Hakan; Ramdan, Ramdan (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2025)
Gampong Teungoh Village, located in Meurah Mulia Subdistrict, North Aceh, has experienced a decline in community income due to damaged irrigation systems that hinder agricultural activities during the dry season. This condition has prompted some residents to shift toward home-based businesses (home industry) as an alternative economic strategy. However, limited digital literacy and underdeveloped marketing approaches remain major obstacles to the growth of these enterprises. This community service initiative employed a Participatory Action Research (PAR) approach, utilizing field observations, semi-structured interviews, and direct training. Students from KPM Group 12 conducted visits to two home industry units—peyek kacang (peanut cracker) and tofu production—and implemented a training program on using Instagram as a digital marketing tool. The results indicate that business owners can manage production independently yet face challenges in reaching broader markets. The introduction of Instagram as a promotional platform successfully enhanced digital engagement, expanded consumer reach, and strengthened the branding of local products. Entrepreneurs began receiving orders through social media, demonstrating increased confidence in utilizing technology. Digital marketing through social media has proven to be an effective strategy for improving the competitiveness of home industry products. Simple technology-based interventions can have a tangible impact on strengthening the local economy. Digital marketing through social media has proven to be an effective strategy for improving the competitiveness of home industry products. Simple technology-based interventions can have a tangible impact on strengthening the local economy.